2017
DOI: 10.1002/cem.2965
|View full text |Cite
|
Sign up to set email alerts
|

Impact of time and temperature of storage on the spoilage of swordfish and the evolution of biogenic amines through a multiway model

Abstract: A new multiway/multivariate approach is proposed to study and model the spoilage of swordfish with time and temperature of storage through the profiles of putrescine, spermidine, histamine, tyramine, tryptamine, cadaverine, spermine, and 2-phenylethylamine. The evolution of these biogenic amines in food is a complex process that cannot be characterized by a single parameter but by a modification of the amine profiles. An experimental strategy is designed to determine these profiles in such a way that data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Mendes [17] showed the absence of correlation between the content of histamine or other amines and the spoilage degree of fish. [18] observed that several indexes were not valid to estimate the degree of In this context, a recent work by Ortiz et al [19] showed that both time and temperature of storage, and their interaction, significantly result in mathematically modelling changes on the profile of the amount of BAs in swordfish. It described two different ways of evolution of the content of BAs related to temperature and time of storage, which explained why the quality indexes based on sums or ratios between BAs were not able to describe the evolution of the spoilage as was already reported by other authors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendes [17] showed the absence of correlation between the content of histamine or other amines and the spoilage degree of fish. [18] observed that several indexes were not valid to estimate the degree of In this context, a recent work by Ortiz et al [19] showed that both time and temperature of storage, and their interaction, significantly result in mathematically modelling changes on the profile of the amount of BAs in swordfish. It described two different ways of evolution of the content of BAs related to temperature and time of storage, which explained why the quality indexes based on sums or ratios between BAs were not able to describe the evolution of the spoilage as was already reported by other authors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The complex paths of synthesis and transformation of these BAs have already been studied [11] and make it necessary to consider not only the correlations between the BAs but the existing internal underlying structure. Multivariate techniques that take the joint changes in the profiles of BAs into account are necessary for that [19].…”
Section: Univariate Correlationsmentioning
confidence: 99%